Choline acetyltransferase may contribute to the risk of Tourette syndrome: Combination of family-based analysis and case–control study. (3rd October 2018) - Yang, Xiuling; Liu, Wenmiao; Yi, Mingji; Zhang, Ru; Xu, Yinglei; Huang, Zuzhou; Liu, Shiguo; Li, Tang
Abstract: Objectives: Twin and family analyses have revealed a genetic contribution to Tourette syndrome (TS) and post-mortem studies have raised the intriguing possibility of a reduction in cholinergic interneuronsin TS patients. Methods: We selected five tag SNPs (rs100824791, rs12264845, rs1880676, rs3793790 and rs3793798) of choline acetyltransferase ( CHAT ) from the Han Chinese population Hapmap database. Genotyping was conducted on 401 TS nuclear family trios and 405 control subjects. Transmission disequilibrium test (TDT) and haplotype relative risk (HRR) analyses were used to analyse the family-based study and a case–control study was also used to assess the genetic susceptibility to TS. Results: The results revealed a significant over-transmission of rs3793790 (TDT, χ 2 = 9.121, P = 0.003; HRR, χ 2 = 6.579, P = 0.01), while case–control analysis found no differences between the two groups (genotype, χ 2 = 0.436, P = 0.804; allele, χ 2 = 0.149, P = 0.700). Also, rs3793798 also indicated a positive association associated with TS (TDT, χ 2 = 5.025, P = 0.028; HRR, χ 2 = 0.250, P = 0.617). However, the other three SNPs investigated were found not to be associated with TS in both in the family-based and case–control studies. Conclusions: Our association analysis demonstrates that CHAT may contribute to TS susceptibility in the Han Chinese population. This gives strong support to the involvement of cholinergic interneurons in the aetiology of TS and reveals a potential therapeutic target.